Girl Thing / Fatimah Rahmat - RAHMAT, FATIMAH (2018)
The company Girl thing Is owned by my sister and I who is in charge in Marketing, Merchandise Controller and Logistics (item postage).The idea of getting this name of the company is due to my passion and addiction to beauty and make ups. I love to look at the best and latest products in stores (and online), and try at home and do it tutorial myself (for company Annual Dinner, etc). I really think that this is useful for make up beginner and to career woman and yes I decided to create a place where I could sell all of my favorites and recommendation.